Effect of la doping on structural, magnetic and microstructural properties of Ba1 - XLaxFe12O19 ceramics prepared by citrate combustion process - S. Ounnunkad (2018)
La-substituted M-type barium ferrites, Ba1 - xLaxFe12O19, with x = 0.00-0.30 were successfully prepared via a citrate combustion process. Properties of the ceramics were characterized by powder X-ray diffraction, vibrating sample magnetometry and scanning electron microscopy. XRD patterns revealed only magnetoplumbite structure without minor phases. With increasing the La substituted content, the saturation magnetization (MS) was increased and reached to a maximum at x = 0.15 and then decreased but coercivity (HC) was increased. SEM micrographs of the dense ceramics showed the hexagonal platelet shape at low La content and the irregular shape at high La content. © Springer Science + Business Media, LLC 2006.